Reading Questions Taxonomy in English Student’s Worksheet Based on Revised Bloom’s Taxonomy - Christian Rispande Siregar; Ade Aini Nuran (TRANSFORM : Journal of English Language Teaching and Learning, 2023)
Reading as one of the crucial skill in English language usually hard to comprehend by the students. To achieve the reading comprehension, teacher has to provide the equipment to measure the students understanding. Worksheet as the appropriate equipment to measure students understanding, generally using the LOTS level of questions rather than HOTS level of questions. In fact, the LOTS level of questions cannot increase the students’ comprehension critically. Worksheet should be selected by the appropriate level of reading questions. It can be analyzed by using the Revised Bloom’s Taxonomy. This study aims to find out; (1) the level of reading questions taxonomy in English student’s worksheet based on Revised Bloom’s Taxonomy, (2) the distribution level of question’s taxonomy in English students worksheet based on Revised Bloom’s Taxonomy. The descriptive qualitative research design with research instruments in the form of document analysis and checklist was employed in this research. The research implied the dominant level of questions is remembering level with 35 items out of 58 questions (60.34%). Followed by understanding (20.68%), creating (10.34%), analyzing (3.44%), evaluating (3.44%) and applying (1.72%)